Group-Based Care in Adults and Adolescents With Hypertension and CKD: A Feasibility Study - Johns, Tanya S. (Kidney Med, 2020)
RATIONALE & OBJECTIVE: Group-based care provides an opportunity to increase patient access to providers without increasing physician time and is effective in the management of chronic diseases in the general population. This model of care has not been investigated in chronic kidney disease (CKD). STUDY DESIGN: Randomized controlled trial in adults (n = 50); observational study in adolescents (n = 10). SETTING & PARTICIPANTS: Adults and adolescents with CKD and hypertension in the Bronx, NY. INTERVENTION: Group-based care (monthly sessions over 6 months) versus usual care in adults. All adolescents received group-based care and were analyzed separately. OUTCOMES: Participant attendance and satisfaction with group-based care were used to evaluate intervention feasibility. The primary clinical outcome was change in mean 24-hour ambulatory blood pressure. Secondary outcomes included physical activity, medication adherence, quality of life, and sodium intake as assessed by 24-hour urinary sodium excretion and food frequency questionnaires. RESULTS: Among adults randomly assigned to group-based care, attendance was high (77% of participants attended ≥3 sessions) and most reported higher satisfaction. Mean 24-hour ambulatory systolic blood pressure decreased by −4.2 (95% CI, −13.3 to 5.8) mm Hg in group-based care patients compared with usual care at 6 months but this was not statistically significant. Similarly, we did not detect significant differences in health-related behaviors (such as medication adherence, sodium intake, and physical activity) or quality-of-life measures between the 2 groups. Among the adolescents, attendance was very poor; self-reported satisfaction, although high, did not change from baseline compared with the 6-month follow-up. LIMITATIONS: Small study size, missing data. CONCLUSIONS: Group-based care is feasible and acceptable among adults with hypertension and CKD. However, a larger trial is needed to determine the effect on blood pressure and health-related behaviors. Patient participation may limit the effectiveness of group-based care models in adolescents. FUNDING: National Institutes of Health R34 DK102174. TRIAL REGISTRATION: https://clinicaltrials.gov/show/NCT02467894.